2007
DOI: 10.1007/s10719-007-9058-8
|View full text |Cite
|
Sign up to set email alerts
|

Isoenzyme-specific differences in the degradation of hyaluronic acid by mammalian-type hyaluronidases

Abstract: Bovine testicular hyaluronidase (BTH) has been used as a spreading factor for many years and was primarily characterized by its enzymatic activity. As recombinant human hyaluronidases are now available the bovine preparations can be replaced by the human enzymes. However, data on the pH-dependent activity of hyaluronidases reported in literature are inconsistent in part or even contradictory. Detection of the pH-dependent activity of PH-20 type hyaluronidases, i.e. recombinant human PH-20 (rhPH-20) and BTH, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…HYAL-1 was found to have maximal and complete HA-degrading activity at pH 3.5-4.0, which is consistent with its role as a HA-degrading enzyme within the lysosome. PH-20 continuously degrades HMW-HA to small oligosaccharides at pH 4.5; at pH 5.5, HA is degraded to larger fragments (54). Unfortunately, the other hyaluronidase proteins were not examined in this study, but the authors speculate that the pH dependence of these enzymes could lead to different biological responses based on the production of different-sized HA fragments at the site of action.…”
Section: Hyaluronans and Lung Diseasementioning
confidence: 95%
See 1 more Smart Citation
“…HYAL-1 was found to have maximal and complete HA-degrading activity at pH 3.5-4.0, which is consistent with its role as a HA-degrading enzyme within the lysosome. PH-20 continuously degrades HMW-HA to small oligosaccharides at pH 4.5; at pH 5.5, HA is degraded to larger fragments (54). Unfortunately, the other hyaluronidase proteins were not examined in this study, but the authors speculate that the pH dependence of these enzymes could lead to different biological responses based on the production of different-sized HA fragments at the site of action.…”
Section: Hyaluronans and Lung Diseasementioning
confidence: 95%
“…Six hyaluronidase genes encode HYAL-1, -2, -3, and -4, PHYAL1 (a pseudogene), and PH-20 (27, 130 -132). A recent study by Hofinger et al (54) revealed that HA degradation by hyaluronidase enzymes may be pH-dependent. HYAL-1 was found to have maximal and complete HA-degrading activity at pH 3.5-4.0, which is consistent with its role as a HA-degrading enzyme within the lysosome.…”
Section: Hyaluronans and Lung Diseasementioning
confidence: 99%
“…PH20 is unique as a membrane-bound, neutral active enzyme with high specific activity toward HA in vitro and in vivo, which is capable of degrading matrix-associated megadalton HA polymers to small tetrasaccharide and hexasaccharide products (16)(17)(18)(19). Given the rapid endogenous turnover of HA, accumulation in tumors could involve disequilibrium between the enzymes that synthesize HA and the enzymes that catabolize HA or receptors for cellular uptake, which subsequently mediate intracellular metabolism (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…The content of HA in tissues is controlled in mammals by two classes of enzymes: HA synthases (HAS1, HAS2 and HAS3) (47) and hyaluronidases (48,49). Particular isoforms of HAS probably synthesize HA of different sizes (50).…”
Section: Discussionmentioning
confidence: 99%